2010
DOI: 10.2298/jas1002195s
|View full text |Cite
|
Sign up to set email alerts
|

Natural process and use of natural matters in organic viticulture

Abstract: During recent years organic viticulture has been developing in the leading viticulture countries worldwide. The organic viticulture has been defined as the application of procedures of organic agriculture in view of increasing the production of top quality grape and wine. All the aspects of the organic viticulture such as cultivating and maintaining the soil, ground cover plants and weed control, balanced nutrition of grapevine, growing systems, disease and pest control are carried out in view of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
8
0
4
Order By: Relevance
“…This may be ascribed to the youth of the plantation (3 rd year), given that in 2018 the yield was comparable to those reported above. Concerning Ravaz indices, values in the 5-7 range are advised to avoid imbalances in the vine, although other authors have suggested a wider range (5)(6)(7)(8)(9)(10)(11)(12), depending on the cultivar, load, irrigation dose and driving systems [58,59]. Very high values-above 10-indicate that the vine has produced a lot of grape for its vigor, that is, that it presents a mismatch due to excess of production or defect in vigor.…”
Section: Discussionmentioning
confidence: 99%
“…This may be ascribed to the youth of the plantation (3 rd year), given that in 2018 the yield was comparable to those reported above. Concerning Ravaz indices, values in the 5-7 range are advised to avoid imbalances in the vine, although other authors have suggested a wider range (5)(6)(7)(8)(9)(10)(11)(12), depending on the cultivar, load, irrigation dose and driving systems [58,59]. Very high values-above 10-indicate that the vine has produced a lot of grape for its vigor, that is, that it presents a mismatch due to excess of production or defect in vigor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the highest classification (Protected Designation of Origin, PDO) requires V. vinifera varieties, hybrids can be used in the next level (called Protected Geographical Indication, PGI). Interspecific, disease resistant hybrids are generally referred to as PIWI (from German: pilzwiderstandsfähig, meaning “fungal disease resistant”) and they are now accepted as V. vinifera varieties in the most European Catalogues [17]. Nowadays “PIWI” is also the name of a producer group devoted to the “dissemination of fungus-resistant grape varieties” with 350 members from 17 European and North American countries, some of whom running private breeding programs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The firsts fungus-resistant varieties, issued from traditional breeding, carried a significant percentage of non-V. vinifera species in their genetic and were therefore considered as "interspecific hybrids" [3]. Based only on phenotypic evaluation data, it is hardly feasible to track the accumulation of resistance genes in a new breeding a e-mail: andresouza@epagri.sc.gov.br; caliari@ epagri.sc.gov.br; joaogardin@epagri.sc.gov.br; dalbo@epagri.sc.gov.br; samilasc@yahoo.com.br b e-mail: brighent@epagri.sc.gov.br; albertobrighenti@epagri.sc.gov.br c e-mail: marco.stefanini@fmach.it d e-mail: oliver.trapp@julius-kuehn.de e e-mail: leocir.welter@ufsc.br f e-mail: samilasc@yahoo.com.br line [4].…”
Section: Introductionmentioning
confidence: 99%
“…The use of molecular markers provides a new tool for breeders and may help to overcome this problem [5]. This tool allowed the development of fungus-resistant varieties carrying both disease-resistance genes and a significant percentage (more than 85%) of V. vinifera in their pedigree; those are generally referred to as "PIWI" (from German: Pilzwiderstandsfähige, "disease resistant") and are accepted as V. vinifera varieties in European catalogues [3].…”
Section: Introductionmentioning
confidence: 99%